LB1531B. Administration of the TNF-alpha inhibitor, infliximab, reduces mortality in hospitalized patients with COVID pneumonia. Results of a randomized controlled trial. (15th December 2022) - O'Halloran, Jane A; Anstrom, Kevin J; Kedar, Eyal; McCarthy, Matthew W; Ko, Emily R; Melsheimer, Richard; Boucher, Cynthia; Chang, Soju; Bozzette, Samuel; Powderly, William G
Abstract: Background: Severe COVID-19 infection is characterized by a dysregulated hyperinflammatory state that contributes to morbidity and mortality. Immunomodulatory therapy has been shown to improve outcomes. We investigated if the TNF-alpha inhibitor, infliximab (IFX), provides additional benefit over standard of care. Methods: We conducted a double-blind, randomized, placebo-controlled trial of IFX (single infusion of 5 mg/kg) compared to standard of care (including remdesivir and dexamethasone) in patients hospitalized with COVID-19 pneumonia. The primary outcome was time to recovery by day 29. Key secondary endpoints included 14-day clinical status and 28-day mortality. Results: A total of 1033 patients received study agent (517 assigned to IFX, 516 to common placebo), constituting the analyzed modified intention-to-treat cohort. Mean age 54.8 years, 60.3% were male, 48.6% Hispanic/Latino and 14% Black. Randomization was balanced for severity of illness and comorbidities. Participants randomized to IFX did not show a statistically significant difference in the primary endpoint with a recovery rate ratio of 1.13 (95% CI 0.99-1.27, p=0.0631) compared to placebo. The median (IQR) time to recovery was 8 days (7, 9) for IFX and 9 days (8, 10) for placebo. Patients assigned to IFX were more likely to have an improved clinical status at day 14 (OR 1.32; 95% CI 1.05, 1.66). The 28-day mortality was 10.1% in the IFX arm and 14.5% in the placebo (OR 0.59 (95% CI 0.39, 0.90)), with a 40.7% lower odds of dying in patients receiving IFX. The improvement in mortality was demonstrated in patients requiring low- or high-flow O2 at baseline but not in those requiring mechanical ventilation or ECMO. Subgroup analysis identified the strongest effect in those with baseline CRP >75mg/ml. There was no imbalances in serious adverse events. Secondary infections were similar between groups (IFX 18.0%, placebo 16.5%). Conclusion: Although single-dose IV IFX did not demonstrate statistically significant improvement in time to recovery, it was associated with improvement in clinical status at day 14 and showed a substantial reduction in 28 day mortality compared to standard of care. Disclosures: Jane A. O'Halloran, MD PhD, Janssen Scientific Affairs, LLC: Grant/Research Support Richard Melsheimer, n/a, Janssen Pharmaceuticals, a Johnson & Johnson Company: Employee of Janssen/J&J|Janssen Pharmaceuticals, a Johnson & Johnson Company: Stocks/Bonds William G. Powderly, MD, Merck: Advisor/Consultant.